Republic of Mozambique : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2005)
This Selected Issues paper and Statistical Appendix reviews Mozambique's impressive economic growth, its composition, and its impact on poverty reduction over the past decade. The paper highlights that improvements in total factor productivity, resulting from a stable macroeconomic environment, the implementation of structural reforms, and high inflows of foreign capital and concessional assistance, have been significant. Good progress has been made in reducing poverty and improving social indicators. The paper also takes stock of the tax reform that Mozambique has implemented since 1996.